Properties of Intuitionistic \(β\)-Open Mappings - Singaravelan, A.; Ilango, Gnanambal (Journal of Informatics and Mathematical Sciences, 2017)
The concept of intuitionistic fuzzy set and intuitionistic fuzzy topological space were defined by Atanssov. Later Coker introduced the concept of intuitionistic set and intuitionistic points. He also introduced the concept of intuitionistic topological space and investigated basic properties of continuous functions and compactness. In a recent paper, the concept of intuitionistic \(β\) -open, intuitionistic \(β\)-closure and intuitionistic \(β\)-interior in intuitionistic topological space were defined by Singaravelan. Also some basic properties of intuitionistic \(β\)-open set were discussed. The purpose of this paper is to introduce and study the concept of intuitionistic \(β\)-open mappings and study its properties.